2023
DOI: 10.1007/s00247-023-05721-7
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcome following magnetic resonance imaging as first-line imaging in low-impact pediatric spine trauma: a single-center retrospective observational study

Abstract: Background Pediatric spinal trauma is rare, but the consequences of a missed injury can be devastating. Medical imaging is often needed in addition to physical examination. Conventional radiographs are widely recommended, but their negative predictive value is limited. Computed tomography (CT) is more sensitive but has a higher radiation dose. Magnetic resonance imaging (MRI) has superior soft tissue contrast and lacks ionizing radiation, but it is more expensive and time-consuming. Thus, the deb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…However, in our previous work, we found no missed injuries requiring surgical interventions after MRI as a first-line imaging in low-impact pediatric spinal trauma. 20 Therefore, we are confident that no patients with potentially unstable injuries would have left without adequate follow-up. Because of the excellent sensitivity of MRI, 7 the follow-up imaging may have been applied to patients whose injuries would not have been detected on CT or conventional radiographs and who would not have been followed up without an emergency MRI.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…However, in our previous work, we found no missed injuries requiring surgical interventions after MRI as a first-line imaging in low-impact pediatric spinal trauma. 20 Therefore, we are confident that no patients with potentially unstable injuries would have left without adequate follow-up. Because of the excellent sensitivity of MRI, 7 the follow-up imaging may have been applied to patients whose injuries would not have been detected on CT or conventional radiographs and who would not have been followed up without an emergency MRI.…”
Section: Discussionmentioning
confidence: 93%
“…It has been shown that MRI can safely be used as a first-line imaging modality for low-impact pediatric spinal trauma. 20 The purpose of the current study was to examine the additional value of follow-up imaging after pediatric spinal trauma initially confirmed on MRI. Our hypothesis and practical rationale were that by leveraging the excellent accuracy of MRI in detecting and excluding spinal injuries, the amount of follow-up imaging of patients primarily scanned with emergency MRI could be reduced.…”
mentioning
confidence: 99%
“…Young or distressed children might need anesthesia for an MRI, which may not be needed for CT scanning. Previous studies did not show negative affects concerning anesthesia for MRI in small numbers of pediatric trauma patients [12,14,15,20]. However, the APRICOT trial showed that, especially in children, there are risks concerning anesthesia [21].…”
Section: Discussionmentioning
confidence: 97%
“…Considering the increased risk of leukemia and brain cancer after ionizing radiation for CT scanning in early life, a possible the next step could be magnetic resonance imaging (MRI) after conventional X-ray to reduce the long-term risk of cancer and accurately diagnose or rule out spinal injuries [12][13][14]. Furthermore, MRI is able to visualize non-osseus tissues, contrary to CT scanning [15][16][17]. The new Dutch guidelines, implemented in 2022, incorporate these risks for the pediatric population and advise conventional X-ray as the first step, with dedicated MRI reserved for patients with neurological deficits [14].…”
Section: Introductionmentioning
confidence: 99%